ECOLOGICAL AND ECONOMIC EFFICIENCY OF THE PEAT SORBENTS USAGE FOR SOLVING ENVIRONMENTAL PROBLEMS - Yaroshovets, E.; Remezova, E. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
It is known that currently the content of organic and inorganic toxic impurities in natural objects is several times higher than the maximum allowable concentration, resulting in increased recreational load. The article is devoted to the topical ecological problem of water and soil pollution by emergency oil spills and oil products. Contaminated water has a negative effect on humans, aquatic life, plants, microorganisms and adjacent areas. Peculiarities of oil pollution of aquatic ecosystems are given and methods of water treatment by use of sorbents are considered. One of the most promising and effective methods of water purification - sorption, using vegetable raw materials, peat - is considered and analyzed. The effectiveness of such sorbents in the elimination of oil pollution has been established. The problem of cleaning water bodies, replacing scarce and expensive filters from synthetic and other materials with cheaper and more available from local raw materials are now becoming particularly acute and relevant. It should be noted that obtaining these sorbents is expedient in environmental and economic terms due to the low cost of materials, easiness of production, high sorption properties, the possibility of recycling. The economic possibility of Manevychi district for the development of peat raw materials for further placement of the enterprise for the production of peat sorbents is analyzed. Information on general technical properties of peat of Koza-Berezina deposit in Manevychi district of Volyn region is analyzed. The article considers the ecological and economic feasibility and proposes the use of peat in the region in the production of oil sorbents.
Keywords: biosorbent; sorption method; ash content; ecological consequences; oil and refined products; peat; degree of decomposition